High-Performance polyimide particles with angular shape - Cerrón-Infantes, Alonso (2016)
High-performance polymers (HPPs) play an important role in modern technology. Many efforts aim to develop cost-effective pathways to synthesize polymers without causing any harm to health and the environment. Polyimides (PIs) belong to the class of HPPs and they show outstanding features e.g. high-temperature stability, resistance to aggressive chemicals and radiation, as well as insulating properties. PI synthesis, however, present yet major challenges. We herein present an alternative approach to PIs of intriguing shape and of impressive size.